Defense policies selection method based on attack-defense signaling game model - Heng-wei ZHANG; Ding-kun YU; Ji-hong HAN; Jin-dong WANG; Tao LI (Tongxin xuebao)
Currently defense policies selection based on game theory mostly applied either the complete information game model or the static game model.In order to be more in line with the reality of network attack and defense,at-tack-defense behavior was studied by dynamic rivalry and incomplete information.The attack-defense signaling game mode was built,the method to quantify policies was improved and an algorithm to obtain the perfect Bayesian equili-brium was proposed.On the basis of analyzing equilibrium,the algorithm for selecting the optimal defense policy was proposed.The simulation experiment demonstrates that the model and algorithms are feasible and effective.By the expe-rimental data,general rules on signaling attack-defense game are summarized,which can guide defenders of different types to make decisions.